Preliminary Phytochemical Analysis and Antioxidants Activities of Ethanolic Extract from Gomphrena serrata Whole Plant - Kodukothanahalli Naganna Nandini; Mekerahalli Narayanappa Palaksha; Belakavadi Shivalingu Mamatha; Anasosalu Ramesh Lekhana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The present study was designed to investigate the phytochemical analysis and antioxidant activities of the whole plant of Gomphrena serrata. Gomphrena serrata widely distributed in South America, North America, and India. These plant parts are used as traditional medicine for the treatment of several ailments. This study aims to assess the phytochemical and free radical scavenging of ethanolic extract of G. serrata present in the plant. The preliminary phytochemical study was performed by standard method. The whole plant of G. serrata proved the presence of bioactive constituents such as carbohydrates, alkaloids, steroids, glycosides, triterpenoids, protein and amino acids, saponins, as well as flavonoids. The in-vitro antioxidant study was performed on the ethanolic extract of shade-dried of the whole plant, which determined by hydrogen peroxide, hydroxyl radical, and 1,1-diphenyl-2-picrylhydrazyl (DPPH) 100 µg/ml assay and was compared to ascorbic acid. The ethanolic extract of the whole plant of G. serrata shows the strong free radical scavenging activity. The present study was the proof for ethanol extract of G. serrata which have medicinally significant and bioactive compounds since these plant species are used as traditional medicine for the treatment of various diseases.